Limitations of Classical Logic and Capabilities of Non-Classical Systems from the Point of View of Artificial Intelligence Development - Hovhannisyan, Hovhannes O. (Տիգրան Մեծ)
The article analyzes the differences between classical and non-classical logical concepts. The features and possibilities of transformational logic are considered. Specific details and proposals are analyzed, including using the example of the functioning of ChatGPT, where the use of transformational logic tools, namely rules that clarify the meaning of explicit forms of thought and derive new judgments from explicit forms of thought, as well as complex rules with the help of which it is possible to simultaneously solve the two problems mentioned, would significantly expand the possibilities and improve the operation of artificial intelligence (AI) systems. Non-classical logical systems, partly critical of classical logic systems, not only open up new prospects for studying thought structures, but also consider issues that go beyond the subject area of classical logical systems, adding the possibilities of logical science. In terms of interpreting the phenomenon of complementarity of logical concepts, the conception of polylogic by G. Brutian is valuable and the application of his ideas will give positive results from the point of view of further development of artificial intelligence tools.
Keywords: Artificial Intelligence